2012
DOI: 10.1016/s0034-7094(12)70161-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Occupational Profile of Anesthesiologists Practicing in Belo Horizonte, Minas Gerais – Brazil, in 2010

Abstract: The population studied indicates that the anesthesiologist is a professional rather overloaded, which corroborates trends seen in the medical field. Major attention should be given to these professionals who live surrounded by harmful occupational hazards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The evaluation of mental disorders in health workers has evidenced their occurrence in different contexts: a registering of mental disorders in 14% of the nurses from two teaching hospitals in Sydney, Australia (Perry, Lamont, Brunero, Gallagher, and Duffield, 2015); 42% of work-related mental disorders, 29% depression, and 24% anxiety, in Dutch hospital doctors (Ruitenburg, Frings-Dresen, and Sluiter, 2012). In Brazil, a high prevalence of CMD in health workers is observed, ranging in 10.3% in anesthesiologists in Belo Horizonte, MG (Neves and Pinheiro, 2012) to 48.6% in Community Health Agents of Pelotas, RS (Knuth et al 2015). A CMD prevalence of 21% among healthcare workers in the Primary Care in Salvador (BA) (Oliveira and Araújo, 2018) and of 25% among female health workers in the Primary Care of Feira de Santana (BA) (Carvalho, Araujo, and Bernardes, 2016) is also worth noting.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of mental disorders in health workers has evidenced their occurrence in different contexts: a registering of mental disorders in 14% of the nurses from two teaching hospitals in Sydney, Australia (Perry, Lamont, Brunero, Gallagher, and Duffield, 2015); 42% of work-related mental disorders, 29% depression, and 24% anxiety, in Dutch hospital doctors (Ruitenburg, Frings-Dresen, and Sluiter, 2012). In Brazil, a high prevalence of CMD in health workers is observed, ranging in 10.3% in anesthesiologists in Belo Horizonte, MG (Neves and Pinheiro, 2012) to 48.6% in Community Health Agents of Pelotas, RS (Knuth et al 2015). A CMD prevalence of 21% among healthcare workers in the Primary Care in Salvador (BA) (Oliveira and Araújo, 2018) and of 25% among female health workers in the Primary Care of Feira de Santana (BA) (Carvalho, Araujo, and Bernardes, 2016) is also worth noting.…”
Section: Introductionmentioning
confidence: 99%
“…Five were presented only as conference abstracts and two were letters. The topics covered were burnout (n = 8) [43–50]; depression (n = 2) [51, 52]; occupational stress (n = 3) [53–55]; substance abuse (n = 1) [51]; and well‐being (n = 1) [56]. The studies that gave a prevalence for burnout in samples of anaesthetists reported proportions of 44% [44] to 78% [50].…”
Section: Resultsmentioning
confidence: 99%
“…[ [53][54][55]; substance abuse (n = 1) [51]; and well-being (n = 1) [56]. The studies that gave a prevalence for burnout in samples of anaesthetists reported proportions of 44% [44] to 78% [50].…”
Section: Surveys Related To Other Mental Health Conditions (Category C)mentioning
confidence: 99%
“…In these cases, the study was included in more than one category of work and consequently, for some variables (professional category and sample size), the frequency is higher than the number of included studies (n = 89). The included studies described common mental disorders in 26 work categories: teachers and professors (n = 21) [6][7][8][9][10][11][12][13][14][15][31][32][33][34][35][36][37][38][39][40][41][42][43] , nursing staff (n = 20) 7,8,19,20,28,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] , physicians (n=9) 7,19,21,28,46,[59]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Due to the detrimental effects of work conditions on mental health, in Brazil a large number of studies have been conducted aiming to analyze the prevalence and factors associated with common mental disorders among a variety of occupational groups. In general, data indicate high variations in prevalence, since some studies indicate prevalences of common mental disorders exceeding 50% [8][9][10][11][12][13][14][15][16][17][18] while others report prevalences lower than 15% [19][20][21][22][23][24][25][26][27][28] . To our knowledge, no systematic reviews have been conducted aiming to describe the prevalence of common mental disorders among Brazilian workers.…”
Section: Introductionmentioning
confidence: 99%